Geomorfološke značilnosti Rakovega Škocjana - Ferk, Mateja (Georitem, 2011)
Rakov Škocjan is a basin in a small karst plain comprising the Rak Valley and the small basin Podbojev Laz. Bedrock terraces in the basin slopes indicate flattening of the basin floor at the water table level at higher elevations and progressive basin development and transformation with surface water flow. Detailed studies of the surface and subsurface karst features in Rakov Škocjan made it possible to describe the basin's evolution and its development in previous genetic stages. The study ('Geomorphological Characteristics of Rakov Škocjan') based on detailed morphographic mapping, collection of morphometric data, speleological analyses, and granulometric analyses of loamy sediments. A synthesis of the findings shows that the basin's genesis and development was much more complex than described in earlier literature. The basin was formed as a surface karst feature through several development stages in which the locations of springs and ponors had changed. Morphogenetic characteristics resulted in an exceptional variety of karst phenomena in a small area, although the basic water course in the broader regional sense did not significantly change.